2019
DOI: 10.1002/csr.1856
|View full text |Cite
|
Sign up to set email alerts
|

What corporate social responsibility brings to brand management? The two pathways from social responsibility to brand commitment

Abstract: Social responsibility has become a cornerstone of brand management, enabling brand differentiation in a high growth market. By distinguishing between symbolic and utilitarian associations of social responsibility, our study identifies two levers for consumer brand commitment. We posit that utilitarian associations enhance consumer brand commitment by strengthening consumer trust. We also argue that brands can encourage consumer commitment through their environmental and philanthropic engagements by conveying v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 62 publications
(133 reference statements)
0
56
0
8
Order By: Relevance
“…Second, they promoted their products among the most vulnerable populations by providing them free of cost. Third, the promotion of actions linked to social responsibility could contribute to create positive associations with brands in the general public, which can increase brand loyalty and purchase intention (26) . Finally, donations provided the opportunity to the industry of ultra-processed products to shape the policy agenda by creating the impression that they can provide solutions to overcome the health challenges created by COVID-19 (38) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, they promoted their products among the most vulnerable populations by providing them free of cost. Third, the promotion of actions linked to social responsibility could contribute to create positive associations with brands in the general public, which can increase brand loyalty and purchase intention (26) . Finally, donations provided the opportunity to the industry of ultra-processed products to shape the policy agenda by creating the impression that they can provide solutions to overcome the health challenges created by COVID-19 (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Marketing analysts have recommended brands to stay active in social media and to show themselves as emphatic and supportive, for example, by showing support to communities during the pandemic or supporting social distancing (24) . Such messages are expected to create positive associations and provide legitimacy, which increases consumers' trust in the brand, quality perceptions, purchase intention and brand loyalty (25,26) .…”
mentioning
confidence: 99%
“…Firms have used corporate social responsibility (CSR) as a major tool to enhance relations between firms and customers (Korschun, Bhattacharya, & Sen, ) as well as to promote positive customer perceptions toward firms (Bhattacharya, Korschun, & Sen, ). A firm's CSR increases brand value and enhances its image, stimulates consumers' buying behaviors, including their brand commitment, and improves its performance and reputation by meeting customer expectations (Abid, Abid‐Dupont, & Moulins, ; Ali, Danish, & Asrar‐ul‐Haq, ; Brown, ; Kowalczyk & Kucharska, ; Luo & Bhattacharya, ; Rothenhoefer, ; Sen & Bhattacharya, ). Prior research has revealed the positive effect of CSR on consumer evaluations of a firm, which, in turn, increases the intention to purchase the firm's product and services (Cuesta‐Valiño, Rodríguez, & Núñez‐Barriopedro, ; Ellen, Webb, & Mohr, ; Mohr & Webb, ; Sen & Bhattacharya, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reveal the positive impact of communicating CSR initiatives among consumers (Abid et al, 2019;Li et al, 2019;Martínez, Herrero, & Gómez-López, 2019). However, this impact may vary according to the type of initiative (Peloza & Shang, 2011;Tully & Winer, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In spite of the different studies in the field of marketing focusing consumer response to CSR messages (Abid, Abid-Dupont, & Moulins, 2019;Li, Liu, & Huan, 2019), much remains to be explored in the field. In this regard, not all CSR initiatives have been approached with the same intensity (Peloza & Shang, 2011;Tully & Winer, 2014).…”
Section: Introductionmentioning
confidence: 99%